At home with the empire : metropolitan culture and the imperial world - Hall, Catherine; Rose, Sonya O. (Cambridge University Press, 2006)
This pioneering volume addresses the question of how Britain's empire was lived through everyday practices - in church and chapel, by readers at home, as embodied in sexualities or forms of citizenship, as narrated in histories. It will be essential reading for scholars and students of empire.